Corpos que não se sujeitam - Daou, Saada Zouhair (2021)
The present work, through bibliographic research, analyzes whether a legal form built around the category of the subject of law, a product of western Modernity, can encompass bodies for which the legal form was not thought and that were historically excluded from the category of subject of law. Therefore, I demonstrate how the legal form incorporated the category of the modern universal subject and how this category was exclusive, breaking its promise of universality. Thereat, I proceed to analyze how women became subjects of law, ceaselessly demanding this recognition by the legal form. This path is traced with the aim of confronting the legal form, more specifically the category of the subject of law, with the bodies that do not subject to the order sex/gender/desire and with the bodies in which the category women is inscribed, since these bodies seem to be a challenge for the very maintenance of a legal form centered on modern western categories. Ergo, throughout this study, I was interested in analyzing the consequences of the incorporation of the subject woman in a legal juridical form designed for a universal subject, for free and equal men, as well as if the legal form involves encompasses the desensitization of the woman subject operated by Judith Butler's queer theory. I believe that these questions are important insofar as many efforts focused on legal claims have been made by groups historically downgraded with support of the law, which demonstrates that it is necessary to understand the nuances of the relationship between the legal form and these bodies, which are not subject to modern categories and, consequently, as I conclude in this work, are not subject to the legal form itself, at least without losing something in this process of subjection